Knowledge of nursing stuff on radiation protection in a public hospital - Zindrou, Konstantina; Kelesi, Martha; Toulia, Georgia; Stoufis, Nikolaos; Babatsikou, Fotoula; Marvaki, Aikaterini (Health & Research Journal, 2016)
Introduction: The ever-evolving applications of radiology-radiotherapy, apart from the solutions offered in daily diagnostic and therapeutic problems, expose healthcare workers to the risk of irradiation and its consequences. Aim: The aim of the present study was to evaluate nurses’ knowledge on the risk of radiation during the daily work and radiation protection instructions to be followed during their participation in diagnostic and therapeutic procedures involving radiation use. Method and Material: The studied sample consisted of 110 nurses working in Public General Hospital of Athens in clinical departments and units so as in laboratories using mainly radiation such as the CT scanner and the catheterization laboratory. For data collection, a special designed questionnaire with questions that reach key areas of the applied radiation protection policy of this hospital was used. Data analysis was performed with the statistical package Statistical Package for Social Sciences (SPSS). Results: The majority (87.3%) of the participants were women, with an average age of 39.66 years (± 7.33 years). The best part of the nurses who participated in the study (82.7%) has not attended any training program concerning radiation protection. Forty percent (40%) of the participants say they do not know the policy of their hospital on issues of radiation protection, while 45.5% did not know whether their working section met the prescribed radiation safety criteria. Participants working in radiology sector had significantly higher degree of agreement with the proposals concerning the applied radiation protection policy compared with participants who worked either in pathological and surgical field or in the operating room and the ICU (p = 0.002). Conclusion: All health professionals (doctors, nurses, technicians), should be constantly informed of all the rules related to both personal protective equipment and protective measures of the patient and the environment against radiation, and the rules applied for the proper use of the appropriate equipment.